A glance into the black box: Novel species-specific quantitative real-time PCR assays to disentangle aquatic hyphomycete community composition. (December 2019) - Baudy, Patrick; Zubrod, Jochen P.; Röder, Nina; Baschien, Christiane; Feckler, Alexander; Schulz, Ralf; Bundschuh, Mirco
Abstract: Aquatic hyphomycetes (AH) are ubiquitous fungi playing a key role in the decomposition of leaf litter in streams. Though their functional performance is modulated by their community composition, this ecological relationship remains poorly investigated due to a lack of suitable methods to identify the biomass-contribution of individual species to AH communities. We, therefore, designed and validated TaqMan® probe-based qPCR assays targeting ten AH species common in temperate regions, allowing detection and quantification of these species within complex communities. In a further step, we compared qPCR-obtained DNA levels to concentrations of the traditional fungal biomass proxy ergosterol. We demonstrate that the qPCR assays are valid for use and that DNA and ergosterol concentrations were significantly positively correlated, suggesting DNA levels as a suitable species-specific biomass proxy. Accordingly, the use of these assays may facilitate multi-species experiments to address major research issues in stress and community ecology including biodiversity-ecosystem functioning relationships. Highlights: We developed 10 qPCR assays to study aquatic hyphomycete community composition. qPCR-obtained DNA levels were shown to be promising taxon-specific biomass proxies. These novel tools open new research avenues in community and stress ecology.